OIL AND GAS. REGIONALLY OWNED ENTERPRISES AND REGIONAL DEVELOPMENT IN POLICY, ENVIRONMENT, AND HEALTH : 978-606-95069-0-5 - Wulandari, Sekar Nur (Technium Books, 2024)
The book: OIL AND GAS REGIONALLY OWNED ENTERPRISES AND REGIONAL DEVELOPMENT IN POLICY, ENVIRONMENT, AND HEALTH ISBN 978-606-95069-0-5 is published in Technium Books. Authors full list: Sekar Nur WuLandari, Herie Saksono, NuruL Izzati, Raymond Rayendra Elven, Endriana Wahyu Alita, Hadi Supratikta, Aliffisya Ummu Raihan, Tedy Kardana, Risa Adelina Tarigan, Amalia Ida Gunawati, Andini Putri Titasari, Kurnia Tri Hermawan, Husnah Rahman, Gema Bangsawan, Charles Conrad Rambung, Fitri Susiyanti, Andi Tenri Awaru, Hasniati, Bachtari ALam Hidayat, Mutiara Kartika Dewi, Romasta Napitupulu, Rina Kumala Dewi, Asriani, Indah Gilang Pusparani, Miftahul Jannah Nasution, Novid Gumelar, Andjar Prasetyo, Ira Amanda Hirbasari